“Unanswered questions”: Acceptability of a personalised breast cancer screening strategy in lower-risk women by healthcare professionals in the context of the MyPeBS study - Celmira Laza-Vásquez; Marta Román; Suzette Delaloge; Sandrine De Montgolfier; Xavier Castells (PLoS ONE, 2026)
Background Based on the relevant differences in breast cancer risk, strategies for personalizing population screening have been proposed. The present study was conducted in the context of the MyPEBS study, which seeks to improve the evidence on the benefits and risks of implementing personalized screening. We explored the views of healthcare professionals involved in the MyPeBS study on the acceptability to extend the screening interval in women at lower risk, as proposed by MyPeBS. Methods Qualitative interpretative descriptive study. Twelve health professionals were interviewed individually and in a discussion group. The transcripts were analysed using thematic analysis. Results For healthcare professionals, the low risk estimate was good news for women. However, the acceptability of decreasing screening frequency was not homogeneous. A lower uptake seemed to be mainly influenced by previous participation in current population-based screening. Several uncertainties were raised for acceptability: the benefits of such personalization for lower-risk women, how to guarantee equity, and the feasibility of this de-escalation in terms of human and financial resources. Conclusion Previous participation in screening was the most significant factor for women’s low acceptance of decreasing screening frequency. Future research should refine the views of health professionals and women. Recommendations should be made to promote participation in personalized screening of women at lower risk.